The α1AT and TIMP-1 Gene Polymorphism in the Development of Asthma. (21st November 2012) - Kumar, Manish; Bhadoria, D. P.; Dutta, Koushik; Kumar F., Mitesh; Singh, Bharat; Singh, Seema; Chhillar, Anil K.; Behera, D.; Sharma, G. L.
Abstract : Asthma has been an inflammatory disorder accompanied by tissue remodeling and protease-antiprotease imbalance in lungs. The SNPs of alpha-1 antitrypsin ( α 1 AT ) and tissue inhibitor of metalloproteinase-1 ( TIMP-1 ) genes were studied for their association with asthma. Genotyping of α 1 AT and TIMP-1 genes was performed in 202 asthmatics and 204 controls. Serum levels of α 1 AT, TIMP-1 and cytokines were estimated to find if the interplay between genotypes and cellular biomarkers determines the pathogenesis of asthma. The analysis of results showed significantly low level of α 1 AT in the serum of asthmatics as compared to controls (P = 0.001 ), whereas cytokines were elevated in patients. No significant difference was observed in the concentration of TIMP-1 in patients and controls. Genotyping led to the identification of 3 SNPs (Val213Ala, Glu363Lys, and Glu376Asp) in α 1 AT gene. The novel SNP Glu363Lys of α 1 AT was found to be associated with asthma (P = 0.001 ). The analysis of TIMP-1 gene showed the occurrence of seven SNPs, including a novel intronic SNP at base G3774A. The allele frequency of G3774A and Phe124Phe was significantly higher in asthmatics as compared to controls. Thus, the SNP Glu363Lys of α 1 AT and G3774A and Phe124Phe of TIMP-1 could be important genetic markers for use in better management of the disease.